O paradoxo de Rousseau: a relação entre liberdade e dever - seguido de breve comparação ao viés teleológico de Kant - Kohn, Ananda Mila (2013)
Beginning with an analysis and valuation of Rousseau's conception of human nature, the theme of freedom tied to social, political and moral duties are investigated. Initially, the idea of nature is shown in order to clarify in what extent this concept plays a role in the political foundation, the concern that follows refers to the legitimacy of social systems. It is advocated that there is no choice between individual or collective spheres, but a condition of mutual coexistence, i.e., the condition for individual freedom lies in the collective comprehensiveness and vice versa. Thereby, the supremacy of the power of any individual over people is supposed to be rejected, and thus the prominence of the law is given, as the one that can compel mankind to fulfill their duties and at the same time, keeping them free, however this only applies to laws that are self-imposed. At that moment, the difference between natural freedom and civil freedom is emphasized, conferring greater importance to the latter. That s because there is, as understood, an inspiration of the freedom possible in society civil freedom in natural freedom, yet, not a derivation from one to another. It is scrutinized the specific requirements of the state of society, according to Rousseau, for the maintenance of freedom, among which it is highlighted the need of not confuse the picture of civil state with the state of nature, on pain of annulment of freedom. The third chapter, where it is presented the moral and political thinking of Kant, provides a comparison of the Kantian thought with Rousseau regarding the passage from the state of nature to the civil state, stressing the idea of progress, very present in the Kantian philosophy. Therefore, this work aims to delineate, firstly, the relation between freedom and duty in Rousseau, in order to demonstrate their mutual need, and reject the idea that the fulfillment of duties shies away the freedom. Secondly, the curious relation between Rousseauvian and Kantian thoughts is unfolded, having in Kant an intensification of some Rousseauvian facets, but also crucial divergence between their theories.